Analysis of Feature Extraction Methods for Speaker Dependent Speech Recognition - Kaur, Gurpreet; Srivastava, Mohit; Kumar, Amod (International Journal of Engineering and Technology Innovation, 2017)
Speech recognition is about what is being said, irrespective of who is saying. Speech recognition is a growing field. Major progress is taking place on the technology of automatic speech recognition (ASR). Still, there are lots of barriers in this field in terms of recognition rate, background noise, speaker variability, speaking rate, accent etc. Speech recognition rate mainly depends on the selection of features and feature extraction methods. This paper outlines the feature extraction techniques for speaker dependent speech recognition for isolated words. A brief survey of different feature extraction techniques like Mel-Frequency Cepstral Coefficients (MFCC), Linear Predictive Coding Coefficients (LPCC), Perceptual Linear Prediction (PLP), Relative Spectra Perceptual linear Predictive (RASTA-PLP) analysis are presented and evaluation is done. Speech recognition has various applications from daily use to commercial use. We have made a speaker dependent system and this system can be useful in many areas like controlling a patient vehicle using simple commands.